Enhanced Geometrical Self-calibration of planar CT - Erfan Bagheri; Amirhossein Saedpanah; Hamidreza Safari; Pouya Parvizian; Abbas Mohammadkazemi; Seyed Roohollah Hosseini (e-Journal of Nondestructive Testing)
Geometrical calibration of Cone Beam Computed Tomography (CBCT) systems is essential for achieving accurate image reconstruction and enhancing spatial resolution. A modern application of these systems is planar CT imaging (Computed Laminography), which is particularly effective for imaging flat objects, such as printed circuit boards (PCBs). Among the existing calibration approaches, self-calibration, which primarily utilizing mutual information as a similarity measure, has garnered significant attention[1]. In this study, we propose the use of regional mutual information[2] as an alternative similarity metric. Our findings demonstrate that regional mutual information enhances calibration accuracy and computational cost, offering a promising advancement in this field.